Metodologias ativas na formação de profissionais da saúde : a experiência de docentes - Grapiglia, Ana Paula (2021)
This research is linked to the line of Teacher Education and Educational Public Policies, of the Graduate Program in Education at Universidade Federal Rondonópolis. The teachers' experiences in using active methodologies in the training processes of health professionals were investigated. In this research, active methodologies are characterized as the practices of teachers used in the classroom that allows the student to be actively involved in their training process, being aware and participate in all teaching moments. As a basis for carrying out this investigation, the following question was used: what is the conception of the teacher who works in this perspective, using active methodologies in the training of health professionals? In the search for answers, it was stipulated as a general objective: to understand the conception of the teacher when using the active methodologies in the training of health professionals; and to detail the information as specific objectives, the following were outlined: to identify the main active methodologies used in undergraduate courses in nursing and medicine; analyze the use of active methodologies in the practice of teachers, and understand how active methodologies are developed in the training of health professionals. Twelve professors from the UFR nursing and medicine courses participated in this research. Data collection was carried out through semistructured interviews in an online and individual way, occurring after the participants signed the Free and Informed Consent Form. Subsequently, the interviews were transcribed and subjected to data analysis, which was organized in groups aimed at specific objectives. The construction of the research writing was structurally organized into four chapters, where in the first chapter I describe the methodological path of the research; in the second section, theoretical contributions referring to education, teacher training, and pedagogical practice aimed at higher education and the health area; in the third chapter I theorize the active methodologies, history, concepts, and freirianos bases; in the fourth and last chapter I conduct a discussion of the data obtained and contextualize it with the theoretical questions studied with a focus on the teachings left by Paulo Freire. When discussing this theme, several aspects related to its effectiveness could be highlighted and confirmed. In this one it became clear, how much such methodologies can stimulate the growth not only of the student but of the teacher, allowing him to be more open and noticeable the need for changes, making reflections on his actions, evaluating if they are being viable whether or not to exercise their practice. However, innumerable traditionalist issues are still present in the conceptions presented by the teachers, being evident in the need for permanent teacher training so that they can visualize the dimension of growth that the use of active methodologies can provide for themselves and the students. Students, in addition to continuous support from their educational institution for the development of their activities. I think that from the moment that teachers can realize a real understanding of the dimension that active methodologies may have caused, we can then have hopes for an education that is more human and that values everyone's knowledge.